Evaluating bioactivity retention in metabolism: a comparative study of chlorogenic acid and its metabolite dihydrocaffeic acid on antioxidant, anti-inflammatory, and anti-obesogenic activities in vitro - Edwin Estefan Reza-Zaldivar; Daniel A. Jacobo-Velázquez (CyTA - Journal of Food)
This study investigates the bioactivity retention of chlorogenic acid (CGA) and its metabolite dihydrocaffeic acid (DHCA) by comparing their antioxidant, anti-inflammatory, and anti-obesogenic properties in vitro. CGA, found in coffee, fruits, and vegetables, is metabolized into DHCA, potentially enhancing bioactivity. Antioxidant capacity was assessed in Caco-2 cells, with DHCA showing superior activity at lower concentrations than CGA. Anti-inflammatory effects were evaluated in LPS-stimulated RAW 264.7 cells, where DHCA exhibited significant dose-dependent inhibition of nitrite production, surpassing CGA. Anti-obesogenic potential was analyzed in 3T3-L1 cells, with DHCA demonstrating stronger inhibition of adipogenesis and notable downregulation of adipogenic genes like PPARγ and C/EBPα. These results suggest that DHCA’s enhanced therapeutic potential due to its simplified structure and increased bioavailability. This study highlights the importance of metabolic transformations in dietary polyphenols for chronic disease prevention and management.